Rancang Bangun Smart Home Berbasis Mikrokontroller ESP 32 dan Blynk - Puspitasari, Selvi; Munazilin, Akhlis; Lazim, Farihin (Universitas Muhammadiyah Gorontalo, 2024)
This research aims to design and build a smart home system that can be controlled remotely via the Blynk application using an ESP32 microcontroller. This system allows users to control various electronic devices at home, such as lights, fans and other equipment, with a smartphone. By using Internet of Things (IoT) technology, this system is expected to bring comfort, security and efficiency to everyday life. The system development process includes hardware design, microcontroller programming, and user interface development for the Blynk application. We hope that the results of this research can contribute to the development of better and more accessible building technology. This research aims to design and build a simple home system that can control lights and fans automatically. This system uses an ESP32 microcontroller as the main brain and the Blynk application as the user interface. Users can turn lights and fans on and off remotely with a smartphone. Therefore, we hope that this system can increase comfort and efficiency of energy consumption at home.